THE ROLE OF NEONOMINATION IN EXPANDING THE VOCABULARY OF THE RUSSIAN LANGUAGE (Web of Humanities: Journal of Social Science and Humanitarian Research, 2024)
This article examines the role of neonominations in replenishing the vocabulary of the Russian language, and discusses the intralinguistic and extralinguistic causes of the emergence of new speech elements.